2022
DOI: 10.1149/1945-7111/ac65bc
|View full text |Cite
|
Sign up to set email alerts
|

Platinum Nanoparticle Size and Density Impacts Purine Electrochemistry with Fast-Scan Cyclic Voltammetry

Abstract: We demonstrate that the density and shape of platinum nanoparticles (PtNP) on carbon-fiber microelectrodes directly impacts detection of adenosine with fast-scan cyclic voltammetry (FSCV) . Previously, we showed that metal nanoparticle-modified carbon significantly improves adenine-based purine detection; however, how the size and shape of the particles impact electrochemical detection was not investigated. Electrochemical investigations of how the surface topology and morphology impacts detection is necessary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Adenosine undergoes three 2 electron/2 proton oxidations, whereas guanosine undergoes two 2 electron/2 proton reactions. In FSCV, it is well established that detection of the secondary oxidation and tertiary oxidation product (for adenosine) is more difficult than capturing the primary oxidation reaction. Not only do analyses of adenosine and guanosine (Figure S3C,D) show enhanced primary oxidation current at PCMFs, but also we observe increases in conversion of primary oxidation product to secondary oxidation product. We speculate that this improvement in the ratio of secondary to primary peak is a result of local trapping of the purine in the pores, further catalyzing the oxidation reaction.…”
Section: Resultsmentioning
confidence: 71%
“…Adenosine undergoes three 2 electron/2 proton oxidations, whereas guanosine undergoes two 2 electron/2 proton reactions. In FSCV, it is well established that detection of the secondary oxidation and tertiary oxidation product (for adenosine) is more difficult than capturing the primary oxidation reaction. Not only do analyses of adenosine and guanosine (Figure S3C,D) show enhanced primary oxidation current at PCMFs, but also we observe increases in conversion of primary oxidation product to secondary oxidation product. We speculate that this improvement in the ratio of secondary to primary peak is a result of local trapping of the purine in the pores, further catalyzing the oxidation reaction.…”
Section: Resultsmentioning
confidence: 71%
“…52 Here, a holding potential of 0.2 V negates dopamine's positively charged adsorption interactions at the CF's surface at negative holding potentials, creating selective serotonin detection while the addition of a cation exchange polymer on the electrode prevents adsorption of other competing neurochemicals. One class of neurochemicals, purines, has been shown exceptional interest in recent years, 15,19,23,47,48,[53][54][55] particularly adenosine and guanosine, for their neuroprotective roles during brain injury. Several voltammetric waveforms have been optimized for adenosine, guanosine, and even co-detection (Fig.…”
Section: Misunderstood Interfacial Interactions Leading To Poor Selec...mentioning
confidence: 99%
“…7C). 22,23 Although these metal nanoparticles play major electrocatalytic roles in neurochemical detection, metal nanoparticles are known to be ECS Sensors Plus, 2023 2 043601 non-biocompatible and toxic if left in the body, 83 so they pose a possible health hazard when implanted in living tissue. Additionally, we have shown that altering CF's surface functionalization through nitrogen doping (Fig.…”
Section: Lacking Controllability In Surface Chemistry Tunabilitymentioning
confidence: 99%
See 2 more Smart Citations